Student Satisfaction with PSA Services (at ITATS) Service Quality (servqual) and GAP (servqual) methods - Suparjo, Suparjo; Dj Amahala, Ainur Rahmania (Jurnal Teknik Industri; Vol 25 No 2 (2022): September : Jurnal Teknik Industri, 2022)
On condition moment this with increasing condition of the times go ahead , thing this take effect to height desire Public for continue education in universities . Higher education felt by Public could increase Source Power Competent human and quality. This thing in accordance with with vision and mission College is institution maker and great HR producer as bridge inside give birth to product quality for can fight in the global market. By because that , needed knowledge about application from knowledge that has been got and practice work by directly, so that student could practice all Required aspects for plunge to world industry that will do it later by straight away . In order to get realize Thing the and as wrong one requirements Graduated program my undergraduate studies as student must go through a studies field that is work practice. Studies case learn something state or identification later problem analyzed as well as linked listen accepted theory on the bench studying or studies literature. Whereas solving problem is analyze the problems that occur in Institution and attempted look for solving analyzed problem that. Keywords:  service, satisfaction, quality